Localization of tumor necrosis factor alpha in synovial tissues and at the cartilage-pannus junction in patients with rheumatoid arthritis. - Chu, C; Field, M; Feldmann, M; Maini, R (1991)
Using immunoaffinity-purified polyclonal anti-human recombinant tumor necrosis factor alpha (TNF alpha) F(ab')2 fragments and immunohistochemical techniques, the cells that make TNF alpha were localized in the inflamed synovial tissue of patients with rheumatoid arthritis (RA) and osteoarthritis (OA). Anti-TNF alpha antibody-stained cells were demonstrated in 9 of 11 RA and 2 of 4 OA but none of 5 normal synovial membranes examined. In RA, 26-64% of the lining layer cells were positive for TNF alpha. In the interaggregate area, 10-30% of the cells contained TNF alpha, often in a perivascular distribution, and up to 19% of the cells in lymphoid aggregates stained for TNF alpha. Some endothelial cells also stained with these antibodies. In OA tissues, the TNF alpha-containing cells were found predominantly in the deeper layer. Cells containing TNF alpha were also found at the cartilage-pannus junction in all 4 RA specimens examined. Double immunofluorescence analysis demonstrated that most TNF alpha-secreting cells in the RA synovial membrane expressed the monocyte/macrophage marker antigens CD11b and CD14, and a few expressed the T cell marker CD3. Our findings provide histologic evidence that TNF alpha is locally produced in the lining and deeper layers of the synovium by cells of the monocyte/macrophage lineage, supporting its role in inflammation. Further, our findings demonstrate that TNF alpha is produced by cells at the cartilage-pannus junction, which could affect chondrocyte metabolism, leading to the cartilage degradation in RA.